Respostas

2013-06-27T21:10:44-03:00

 x²-x-12=0

 

Δ=(-1)²-4*1*(-12)

Δ=1+48

Δ=49

 

x= -(-1)±√49 = 1±7

          2*1           2

 

x'= 1+7  = 4

        2

x"= 1-7 = -6/2 = -3

        2  

 

S = { 4 , -3 }

19 4 19
2013-06-27T22:57:15-03:00

x²-x-12=0
a=1 b=-1 c=-12
coeficientes: 1, -1 e 12


pela fórmula de báskara:
delta= b²-4.a.c

delta=(-1)²-4.1.(-12)
delta=1+48=49

depois de encontrar o "delta", encontra-se o x
x'=(-b+(raiz quadrada)"delta")/2.a ou
x''=(-b-(raiz quadrada)"delta")/2.a

x'={[-(-1)]+raiz quadrada de 49}/2.1
x'=(1+7)/2=4

x"={[-(-1)]-raiz quadrada de 49}/2.1
x''=(1-7)/2=-6/2=-3

x'=4 e x''=-3

2 5 2